The Effects of Western Culture on Rites of Passage among the Hehe and Bena Societies: Case Study in Iringa Rural District (Global Journal of Human-Social Science, 2025)
This study investigates how Western culture impacts the rites of passage among the Hehe and Bena communities in the Iringa Rural district revealing a complex relationship between traditional customs and modern influences Interviews with community members including elders and youth show a strong commitment to cultural preservation despite economic pressures and lifestyle changes The findings highlight the need to adapt traditional rites by integrating modern elements to maintain relevance for younger generations fostering cultural evolution Western media and educational advancements significantly shape local practices leading to a hybridization of traditions that reflects both resilience and adaptability The study suggests that cultural preservation efforts educational programs and media engagement are vital to sustaining traditional practices within a modern context offering insights into a balanced approach to cultural development In methodology the study employed a mixedmethods approach combining both qualitative and quantitative research techniques to explore the effects of Western culture on the rites of passage among the Hehe and Bena societies in Iringa Rural A case study design was utilized to gather data from various sources including interviews focus group discussions and surveys Respondents representing different community groups were selected using both simple random and purposive sampling methods Data were analyzed using SPSS for quantitative insights and content analysis for qualitative data ensuring a comprehensive understanding of the cultural changes occurring in the region
Keywords: rites of passage; western culture; tourism; cultural tourism